Penerapan Dialogic teaching Melalui LKPD Konsep Kartun untuk Meningkatkan Keterampilan Proses Sains Siswa SMA - Najihah Fakhirah Siregar; Siti Sriyati; Amprasto (Postgraduate, University of Mataram, 2023)
Science learning should focus on cognitive processes that lead to the development of scientific processes, scientific products, and scientific attitudes. However, field facts show that students' science process skills are still low. One possible solution that can train and improve students’ science process skills is dialogic teaching facilitated by concept cartoon worksheets. This study aims to identify the implementation of dialogic teaching through concept cartoon worksheets to improve students' science process skills. This research method is quasi-experimental with 2 sample classes, namely the experimental class and the control class which were taken by purposive sampling. The research instrument is science process skills test, concept cartoon worksheets, learning implementation observation sheet, and student response questionnaires. Data analysis used independent t-test and n-gain. The results showed that students’ science process skills in control class and experimental class were significantly different. The n-gain test results also showed a higher increase in the experimental class than the control class with an average n-gain result of 0.65 (moderate) in the experimental class and 0,31 (moderate) in the control class. Based on these results it can be concluded that the application of dialogic teaching through the concept cartoon student worksheet can improve students' science process skills.